Pengembangan Media Pembelajaran Video Interaktif pada Materi Spldv terhadap Kemampuan Pemahaman Matematis Siswa Kelas X - Maria Ayu Fitri Lestari; Muchtadi Muchtadi; Wandra Irvandi (International Forum of Researchers and Lecturers, 2023)
This study aims to produce interactive video learning media in mathematics learning to improve students' mathematical understanding that is valid, practical and effective. This research is a development research where the research procedure uses a 4D design, namely (Define, Design, Development, and Dissemination) but this research only reaches the Development stage due to limited time, costs and research subjects. The subjects in this study were 26 class X students of SMAN 1 Nanga Tayap. The instrument used by the researcher was a validation sheet to see the validity of interactive video media, a response questionnaire was used to see the practicality of interactive video media and a pilot test was used to see the practicality of interactive video media in improving students' mathematical understanding abilities. Based on the validation of the three validators on learning interactive video media, it can be declared valid with an average index percentage of 79.69% with valid criteria. Material expert validation was declared valid with an average index percentage of 78.88% with valid criteria. Meanwhile, media expert validation was declared valid with an average percentage index of 79.28% with valid criteria. The level of practicality with an average percentage of teacher responses is 80%, with very valid criteria and an average percentage of student responses is 82.66% with very practical criteria. From the results of completing the teacher and student response questionnaire, interactive video learning media for students' mathematical understanding can be stated to be very practical for students. The level of effectiveness of students after using interactive video learning media on mathematical understanding abilities is 80.76% with very effective criteria.